Analysis of coastal tourists' environmental attitudes and potential as education for sustainable development - Fadilah, Solikhah Isti; Surtikanti, Hertien Koosbandiah; Irawan, TB Moh Irma Ari (Universitas Wiralodra, 2024)
Indonesia has abundant natural resources, including tropical rainforests, biodiversity, mineral mines, waters, and coastal areas. Utilization of these resources must be carried out wisely and sustainably to ensure the welfare of future generations. This research aims to evaluate people's attitudes and behavior towards the environment, especially in river and coastal areas in Central Java, Indonesia. The research methods used are surveys, observations and interviews. The survey was carried out by distributing a questionnaire consisting of 30 questions. This statement includes awareness of protecting the coastal and river environment and real actions or behaviors that care about the surrounding environment. Data collected from the survey was analyzed using descriptive statistical analysis techniques to identify general patterns of respondents' attitudes and behavior. The research results show that people's attitudes toward environmental care are in the high category for 49% of respondents and very high for 51% of respondents. These results do not reflect some of the real actions taken by the community, especially in coastal areas. Several factors influencing environmental awareness were analyzed, including age, gender and education level. Researchers found that educational factors significantly affect attitudes towards environmental care. The results of this analysis can be used to support Education for Sustainable Development (ESD) in increasing pro-environmental awareness and action and supporting sustainable development goals.